AN ASSESSMENT BETWEEN ICT NETWORK COMPONENT AND ICT STORAGE ON JUDICIARY PERFORMANCE: CASE OF ELDORET LAW COURTS - Ndombi, Rose Mugeni; Munyua, Jenepher; Mutong’wa, Sanja Michael (International Journal of Research -GRANTHAALAYAH, 2018)
This research seeks to perform an Assessment between ICT Network Component and ICT Storage on Judiciary Performance in Eldoret Law Courts. The questions are: how does ICT Network component influence judiciary performance and does ICT storage influence judiciary performance in Eldoret law courts? The study adopted Correlational research design. The target group was Judges, Magistrates, ICT personnel and Advocates. A sample size of 272 was achieved from a target population of 899 employees in the Judiciary < 0.05 was considered significant. Data will be analyzed by SPSS V 20; regression was used to test the hypotheses. Correlation and multiple regressions were used to measure: Effects. The p <0.05 was considered statistically significant. The study findings indicated that there was a significant relationship between ICT Network component and judiciary performance (p=0.000); there was a significant relationship between ICT Data storage component and judiciary performance (p=0.000).The research conclusion indicate that use of ICT in the judiciary is vital in enhancing access to justice by creating an efficient court system and that access to justice involves making the court system accessible to all who require court services for instance judgments, it further established that ICT storage used by the MIS system in running transactions are effective, but require boosting. The study also concluded that all accessible points should be protected court information via internet. The study recommended that judiciary should adopt ICT initiatives after they have a specific plan in place to do so.